Assessing the impact of cash transfer system–under the livelihood empowerment against poverty program on poverty reduction in Ghana- reflections on North Gonja district; a case study of North Gonja district in Northern Region. - Kilu, Lawal (KNUST, 2025)
A Thesis Presented In Partial Fulfillment Of Th E Requirements For The Degree Master Of Arts In Public Administration.